Mapping coffee intensification in Mexico: a multivariate spatial analysis approach - Galeana-Pizaña, José Mauricio; Manson, Robert H. (Frontiers in Sustainable Food Systems, 2025)
Agroforestry systems, particularly shade coffee farms, offer key ecosystem services such as wildlife habitat, water regulation, and carbon storage. While remote sensing has advanced in detecting land use change from shade coffee to other covers, monitoring subtle shifts from traditional to intensified management remains limited. This study presents a spatial, empirically validated, typology of coffee intensification in eleven coffee-growing regions of southern Mexico. Using k-medians clustering on data from over 178,000 parcels, we classified coffee farms into three levels of intensification—low, medium, and high—based on biophysical, socioeconomic, and livelihood strategy indicators. Field validation with 127 farms showed 76.98% agreement between the Index of Coffee Intensification (ICI) and expert assessments. Significant statistical differences in intensification levels between coffee-growing regions were found using chi-square tests. Overall, 43.1% of farms were low-intensification, 35.2% medium, and 21.7% high. Regions like Costa de Oaxaca and Mixteca had mostly low-intensity systems, while Xicotepec and Cuetzalan showed higher levels of intensification. Highly intensified parcels tended to be larger, used more agrochemicals, and were closer to processing infrastructure, while low-input farms were concentrated in marginalized areas with higher ecological integrity. The ICI showed a moderate but significant correlation with municipal coffee yields (R2 = 0.46), suggesting that intensification affects productivity, but other factors also play a role. Differences in chemical use, commercialization strategies, and infrastructure access highlight the influence of territorial context. These findings reveal a dual structure in Mexico’s coffee landscape and highlight the need for region-specific policy strategies. Unlike deforestation-based monitoring, the ICI offers a new lens to assess ecological change within agroforestry systems, especially in tropical mountain regions, and can help guide the development of more sustainable coffee management policies.